Klimatische und pflanzengeographische Grundzüge Zentralamerikas - Lauer, Wilhelm (ERDKUNDE, 1959)
As regards its plant cover, Central America occupies a special position among the tropical countries of the world. Although in its horizontal and vertical zonation the vegetation is adjusted to the tropical climatic conditions, as regards species, it shows flora elements from boreal areas. The paper investigates first the climate of the area, which appears as genuine tropical diurnal climate up to the highest altitudes. The vegetation is arranged into clitmato-ecological zones and altitudinal belts according to the thermical altitudinal zones (annual isotherms) and the number of humid or arid months, respectively (isohygromens). The floristic investigation shows a more pronounced presence of holarctic and neoarctic elements in the north of the area. Many tropical mountain flora elements have their limit in Costa Rica. Some reach as far as the Mexican mountains. The main reason for the abrupt interruption of plant migration from north or south is the great gap of the mountain range between Honduras and Costa Rica. To sum up, the special position of Central America as regards plant geography is characterised by the striking contrast between climatic ecological unity and floristic diversity.